A new Oreonetides Strand, 1901 from the Russian Far East (Araneae, Linyphiidae) - Tanasevitch, Andrei V. (Zootaxa, 2017)
The genus Oreonetides Strand, 1901 has a highly tangled taxonomic history described in detail by Saaristo (1972), van Helsdingen (1981) and Eskov (1984). At present, the genus contains 17 species confined to the Holarctic Region, including Taiwan (Word Spider Catalog 2017). Amongst the species, seven have hitherto been registered from the Russian Far East (Mikhailov 2013), although the generic allocation of some of them requires revision. In this paper presented description of still one more Oreonetides species collected from the southern part of the Russian Far East.